(untitled) (International Journal of Physiotherapy, 2016)
Background: Froze shoulder in other words adhesive capsulitis is a condition characterized by progressive loss of shoulder mobility with general symptoms of pain, limited range of motion and altered scapula thoracic rhythm. The condition is mostly treated by using traditional physical therapy measures the study was conducted with the aim to determine the efficacy of routine physical therapy treatment with and without Kaltenborn mobilization in reducing pain and increasing shoulder mobility in frozen shoulder patients. Methods: The study was conducted in the department of Physiotherapy mayo Hospital Lahore. A sample of 60 patients was collected by using non-probability, convenience sampling without any discrimination regarding, social economic status, education, out of which there were 8 drop outs. Sample was distributed in two groups (26 participants each) i.e. experimental group receiving routine physical therapy and Kaltenborn Mobilization technique and control group receiving the routine physical therapy only. Participants were recruited based on the inclusion and exclusion criteria. Demographic data and data regarding pain relief was collected using self-made questionnaire and penn shoulder scale questionnaire respectively. Results: Results were evaluated by using SPSS version 19.1 it was seen that range of motion of cervical region was greater for the experimental group than control group. The maximum PENN score achieved in control group were 51 however for experimental group the value was 64. Conclusion: It was concluded that kaltenborn mobilization is an effective means of treating frozen shoulder and when combined with routine physical therapy gives better results.